Cash up to contractual process of minimal amount in retail and Superior National University of Colombia (2014)
Recruitment is the activity through which goods and services with resources that are allocated for the implementation of research, extension and teaching at the National University of Colombia are acquired; activity that must be developed in compliance with established standards and properly regulated in order to avoid incurring errors that can be developed into research for internal and external control agencies and in some cases could become legally sanctioned , leading to wear and an administrative therefore a patrimonial detriment. This paper summarizes the stages of the recruitment process for contractual minimum orders , lower and higher rates according to the classification established in the contractual arrangements of the National University of Colombia , describes the causes or errors that can be incurred in each and how to mitigate them through the implementation of an effective monitoring strategy .